Fluorofenidone Alleviates Renal Fibrosis by Inhibiting Necroptosis Through RIPK3/MLKL Pathway - Dai, Qin; Zhang, Yan; Liao, Xiaohua; Jiang, Yupeng; Lv, Xin; Yuan, Xiangning; Meng, Jie; Xie, Yanyun; Peng, Zhangzhe; Yuan, Qiongjing; Tao, LiJian; Huang, Ling (Frontiers in Pharmacology, 2020)
Cell death and sterile inflammation are major mechanisms of renal fibrosis, which eventually develop into end-stage renal disease. “Necroptosis” is a type of caspase-independent regulated cell death, and sterile inflammatory response caused by tissue injury that is strongly related to necrosis. Fluorofenidone (AKF-PD) is a novel compound shown to ameliorate renal fibrosis and associated inflammation. We investigated whether AKF-PD could alleviate renal fibrosis by inhibiting necroptosis. Unilateral ureteral obstruction (UUO) was used to induce in renal tubulointerstitial fibrosis in C57BL/6J mice. AKF-PD (500 mg/kg) or necrostatin-1 (Nec-1;1.65 mg/kg) were administered simultaneously for 3 days and 7 days. Obstructed kidneys and serum were harvested after euthanasia. AKF-PD and Nec-1 ameliorated renal tubular damage, inflammatory-cell infiltration, collagen deposition, and the expression of proinflammatory factors (interlukin-1β, tumor necrosis factor [TNF]-α) and chemokines (monocyte chemoattractant protein-1) decreased. AKF-PD or Nec-1 treatment protected renal tubular epithelial cells from necrosis, and reduced the release of lactate dehydrogenase in serum. Simultaneously, production of receptor-interacting protein kinase (RIPK)3 and mixed lineage kinase domain-like protein (MLKL) was also reduced 3 days and 7 days after UUO. AKF-PD and Nec-1 significantly decreased the percentage of cell necrosis, inhibited the phosphorylation of MLKL and RIPK3 in TNF-α- and Z-VAD-stimulated human proximal tubular epithelial (HK-2) cells. In conclusion, AKF-PD and Nec-1 have effective anti-inflammatory and anti-fibrosis activity in UUO-induced renal tubulointerstitial fibrosis, potentially mediated by the RIPK3/MLKL pathway.